Endocentric and Exocentric Compound in Infinite Album by Deep Purple - Dovan Bahana Sakti; Unpris Yastanti; Sayyid Khairunas (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2021)
Morphology is a sub-branch of linguistics that deals with words and the system related to words. Compounding is one of the word-formations is a morphology phenomenon in which two words are enjoined as one. This research focuses on the process of compound words in the song lyrics of Infinite album by Deep Purple. Qualitative-descriptive research is used to analyze and describe the meaning type of the compound words. The writer uses theories from several experts such as Ingo Plag, Laurie Bauer, Geert Booij, Francis Katamba, Carstairs-McCarthy, and Martin Haspelmath, to analyze the meaning type of compound words. There are 37 identified compounding from the entire album with the various formats, lexical head,s, and meaning type. Endocentric is the most dominant compounding with 31 compoundings (83.78%), and exocentric occurs 6 times (16.22%).